Faktor – Faktor yang Berhubungan dengan Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak Sekolah Dasar Kelas III & IV di RW 018 Kecamatan Babelan Kabupaten Bekasi - Amalia, Putri (JURNAL KESEHATAN KARTIKA, 2025)
Background: A healthy lifestyle and hygiene are the result of actions based on self-awareness in preventing health problems. Clean and Healthy Living Behaviors (PHBS) are rooted in an educational process that improves the ability of individuals and families to maintain their health independently and encourages active participation in achieving optimal health. Objective: This study aims to analyze factors related to PHBS behavior among third and fourth grade students in RW 018, North Bekasi Regency. Method: Descriptive analytical with a cross-sectional approach. Data were collected through a structured questionnaire covering the following variables: level of knowledge about PHBS, the role of parents, the role of teachers, the living environment, and the availability of facilities and infrastructure supporting PHBS. Data analysis was performed using the Chi-Square test with a 95% confidence level (α = 0.05). Results: Of the total 32 respondents, 22 students (68.8%) had a good level of knowledge about PHBS, 7 students (21.9%) had adequate knowledge, and 3 students (9.4%) had poor knowledge. Of the five variables studied (knowledge, parental role, teacher role, environment, and facilities and infrastructure), the parental role showed a statistically significant relationship (p = 0.000 < α = 0.05) with PHBS practices. Meanwhile, the other variables showed no significant relationship (p-value > α = 0.05). Conclusion: Parental role is the most influential factor in encouraging the implementation of PHBS in elementary school children. It is hoped that the role of the family in health education will be strengthened so that students have a better understanding and healthy lifestyle habits from an early age.